2019
DOI: 10.5847/wjem.j.1920-8642.2019.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Do medical students studying in the United Kingdom have an adequate factual knowledge of basic life support?

Abstract: BACKGROUND: Healthcare professionals have a duty to maintain basic life support (BLS) skills. This study aims to evaluate medical students' factual knowledge of BLS and the training they receive. METHODS:A cross-sectional, closed-response questionnaire was distributed to the fi rst-and fourth-year students studying at institutions in the United Kingdom. The paper questionnaire sought to quantify respondent's previous BLS training, factual knowledge of the BLS algorithm using five multiple choice questions (MCQ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 13 publications
3
26
1
4
Order By: Relevance
“…In contrast to gender, the results showed that attendance a BLS course previously had signi cant effect on knowledge level. Similar results were reported from Oman, [13] United Kingdom, [18] Pakistan [15] and Thailand [19]. In this study, the numbers of participants who received training about BLS and had knowledge of CPR (massage rate, massage location, massage depth and massage/ventilation rate) were higher than those who did not receive training.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In contrast to gender, the results showed that attendance a BLS course previously had signi cant effect on knowledge level. Similar results were reported from Oman, [13] United Kingdom, [18] Pakistan [15] and Thailand [19]. In this study, the numbers of participants who received training about BLS and had knowledge of CPR (massage rate, massage location, massage depth and massage/ventilation rate) were higher than those who did not receive training.…”
Section: Discussionsupporting
confidence: 87%
“…There was a signi cant difference between the participants from different countries where the mean score in Syria, Jordan and Iraq was 18.3, 24.3 and 18.8 respectively (p < 0.05). The participants were divided into 3 level according to total score; low (0-12), moderate (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) and high (25-37). In total, 18.3%, 72.8% and 8.9% of participants had high, intermediate and low level respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous reports have examined the knowledge and attitudes of BLS among health profession students in different countries, including Pakistan [ 7 ], India [ 8 ], Nigeria [ 9 ], Egypt [ 10 ], and the UK [ 11 ]. Similarly, studies in Saudi Arabia assessed BLS knowledge among medical students in Qassim University [ 12 ], Jouf University [ 13 ], Princess Noura University [ 14 ], Jizan University [ 15 ], and King Khalid University [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Switzerland, as in many other countries, junior medical students only possess limited knowledge regarding basic life support (BLS) procedures [1][2][3][4][5][6]. Medical students are often off-duty when exposed to out-of-hospital cardiac arrests (OHCAs) or to other emergency situations [7].…”
Section: Introductionmentioning
confidence: 99%